(untitled) (IITM Journal of Business Studies, 2024)
Policing is the only arm of the state that is authorized to use coercive force against its citizens, which makes the job uniquely demanding. With the emergence of a work culture characterized by job demands with complex technology, work overload, social isolation, sleep disturbances, and spillover effects leading to work-life imbalance, police work has been identified as one with a highly stressful environment. Despite interest over the years in the predictors and outcomes of police stress, the research findings are inconsistent. No review, to date, has offered a holistic retrospection on the job demands of the police. The current study is an attempt to overview job demands research on police personnel using bibliometric analysis and systematic review of literature. The study highlights the publication trend, the most productive and influential authors, the significant areas of research in the domain, and infers the intellectual structure of job demands research on police personnel. Using the science mapping techniques of co-citation and bibliometric coupling analyses, the study infers the knowledge foundation and the thematic structure of job demands research in police personnel for the period 1983-March 2024 by uncovering six and eight specific areas of job demands research on police personnel respectively. Additionally, by using co-occurrence analysis, the study also attempts to highlight the influential topics of research in the same period divided into four segments and also outlines the future research directions in the domain of job demands with police personnel as the focal point.